Implementation of Decision Support System Method to Evaluate Posyandu Program In Tangerang Selatan - Desanti, Ririn Ikana; Maximus, Jason; Sitorus, Budi Berlinton (Universitas Multimedia Nusantara, 2023)
The goal of this study is to develop a decision support system (DSS) using the Technique for Order Preference by Similarity to Solution (TOPSIS) and Simple Multi-Attribute Rating Technique (SMART) approaches to evaluate the Posyandu Program. The case study focuses on Posyandu in Tangerang Selatan Regional. The local government runs Posyandu, an Indonesian public health service facility for women and children. This DSS system uses the TOPSIS approach to employ the ranking function and select the best alternative based on agreed-upon criteria with the local Posyandu. This approach calculates the distance between each option with a positive ideal solution and a negative ideal solution and then computes the relative preference value, which determines how to rank. In addition, the SMART approach assigns weights to each predefined criterion. Using the TOPSIS and SMART approaches to implement DSS at Posyandu helps people make decisions by providing them with the best ranking results based on predefined criteria. Thus, it is believed that the findings of this study would improve the quality of Posyandu services and contribute to the overall health of the community.